IMPLEMENTASI PEMBELAJARAN TAHSIN QIRO’AH DI JQH PUTRI MA’HAD UNIA PRENDUAN - Mu'iz, Abdul; -, Saliyana (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2024)
Improving the reading is an activity to improve and correct the reading of the Qur'an so that it is in accordance with the reading of the Prophet Muhammad SAW. Many tahfiz institutions implement this reading improvement activity, one of which is Jam’iyyatul Qurra’ wal-Huffaz (JQH) UNIA. JQH UNIA is one of the Quran memorization groups at universities which is intended for students who want to memorize the Quran while studying at a pesantren. This activity is very important, especially for those who memorize the Qur'an to improve their reading of the Qur'an so that they do not make mistakes in reading the Qur'an. When the reading is wrong, it automatically affects the meaning of the Qur'an itself, so that they make mistakes in memorizing the Qur'an. Thus, this activity is very necessary to improve the reading of the Qur'an. The problem raised in this study is how the implementation of reading improvement activity in JQH Putri Ma’had UNIA Prenduan and what are the supporting factors and inhibiting factors in the implementation of reading improvement activity in JQH Putri Ma’had UNIA Prenduan. To find out more about how the implementation of reading improvement activity in JQH Putri Ma’had UNIA Prenduan, a qualitative research type was used through a descriptive approach with data analysis which includes data collection, data reduction, data presentation and conclusions. Data sources include two types: first, primary data, second, secondary data. Data collection techniques used are interview methods, observation and documentation. The results of this study indicate that the implementation of reading improvement activity in JQH Putri Ma’had UNIA Prenduan was held with the aim that JQH members are good at reading and memorizing the Qur'an. The implementation of this activity is every Tuesday night Wednesday by applying the jibril method and the sorogan method. The supporting factors are the high quality of the students' abilities, the skilled and qualified muhaffizah and the yanbu'a book which is the guidebook. While the inhibiting factors are the lack of preparation of the students to advance to muhaffizah and the sudden activities so that  reading improvement activity are not carried out.